Performance traits and indexes of the intake pattern of fattened pigs with fresh paste of whole avocado - Fránquez, Pamela; Rodríguez, G.; Lemus, C.; Grageola, F.; Ly, J. (Cuban Journal of Agricultural Science, 2018)
A total of 16 Yorkshire x Landrace pigs, castrated males and females in a 1: 1 ratio, with an average of 67.0 kg of live weight, were randomly distributed in two treatments, which consisted of diets formulated to contain 0 and 21 % of fresh paste of waste avocado (Persea americana Mill.). The paste was made up of ripe whole fruits, and contained 14.3 % of crude fiber and 49.2 % of ether extract. There was a significant decrease (P = 0.001) in food intake and feed conversion in animals fed with avocado diet (2.34 kg DM/d and 2.75 kg DM/kg gain) with respect to those of the control diet (3.30 kg DM/d and 3.13 kg DM/kg gain). The performance traits were significantly correlated (P = 0.001) between each other. The animals intake less (58.3 %) of the food offered with paste with respect to the offer that did not contain it (74.4 %) (P = 0.143). The ingestion speed decreased from 50.1 to 31.5 g fresh / min (P = 0.027) and from 43.5 to 17.7 g DM/min (P = 0.001). It is suggested that 21 % of fresh paste of waste avocado in the diet influences positively on the feed conversion efficiency of finished pigs, but the weight gain decreases when the voluntary intake of food reduces. Key words: pigs, zootechnics, Persea americana, ingestion speed